Construction of Anisotype CdS/Si Heterojunction and Lineup Using I-V and C-V Measurements - Al-Samarai, Abdul-Majeed E. (Iraqi Journal of Physics, 2009)
Near-ideal p-CdS/n-Si heterojunction band edge lineup has been investigated for the first time with aid of I-V and C-V measurements. The heterojunction was manufactured by deposition of CdS films prepared by chemical spray pyrolysis technique (CSP) on monocrystalline n-type silicon. The experimental data of the conduction band offset Ec and valence band offset Ec were compared with theoretical values. The band offset Ec=530meV and Ev=770meV obtained at 300K. The energy band diagram of p-CdS/n-Si HJ was constructed. C-V measurements depict that the junction was an abrupt type and the built-in voltage was determined from C-2-V plot